PENGARUH KOMPETENSI GURU TERHADAP PRESTASI BELAJAR AKUNTANSI SISWA PROGRAM KEAHLIAN AKUNTANSI SMK NASIONAL AL- HUDA PEKANBARU - ', Helpi; ', Gusnardi; Trisnawati, Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstack: The teacher is a prominent educators, which obliges must have competence in teaching activities. While competence as the knowledge, skills and abilities controlled by someone who has been a part of himself so that he can perform behaviors cognitive, effective and psychomotor the best possible That is to say, the role of teachers in mendidikan increase the student achievement is needed. The learning achievement itself is the acquisition of knowledge or skills developed through subjects, usually indicated by test scores or grades given by teachers. Thus, in this study aims to determine the effect of teacher competence on student learning achievement in accounting National Accounting Expertise Program SMK Al-Huda Pekanbaru. This research is located in Al-Huda National Vocational school Pekanbaru. Data obtained in the form of primary and secondary data. Samples in this study was 56 people. The analysis of this study is a simple linear regression to determine the effect of teacher competence on student achievement. From the results of the analysis, there is the influence of teachers on learning achievement competence with significance of 0.000, and the magnitude of the effect dalah by 45.7%. So from the research conducted, the teachers are required to able to create an effective learning environment, fun, and able to manage the class well and further improve the competence of teachers to attend trainings were conducted by both the school and the education department. Keywords: Teacher Competency and Student Achievement